3-Hydroxykynurenine in Regulation of Drosophila Behavior: The Novel Mechanisms for Cardinal Phenotype Manifestations - Zhuravlev, Aleksandr V.; Vetrovoy, Oleg V.; Ivanova, Polina N.; Savvateeva-Popova, Elena V. (Frontiers in Physiology, 2020)
Dysfunctions of kynurenine pathway of tryptophan metabolism (KPTM) are associated with multiple neuropathologies in vertebrates and invertebrates. Drosophila mutants with altered content of kynurenines are model objects for studying the molecular processes of neurodegeneration and senile dementia. The mutant cardinal (cd1) with accumulation of the redox stress inductor 3-hydroxykynurenine (3-HOK) shows age-dependent impairments of the courtship song and middle-term memory. The molecular mechanisms for 3-HOK accumulation in cd1 are still unknown. Here, we have studied age-dependent differences in spontaneous locomotor activity (SLA) for the wild type strain Canton-S (СS), cd1 and cinnabar (cn1) with an excess of neuroprotective kynurenic acid. We have also estimated the level and distribution of protein-bound 3-HOK (PB-3-HOK) in Drosophila brains and head tissues. The middle-age cd1 show the higher running speed and lower run frequency compared to CS, for cn1 the situation is the opposite. There is a decrease in the index of activity for 40-day-old cd1 that seems to be an effect of the oxidative stress development. Surprisingly, PB-3-HOK level in Drosophila heads, brains and head capsules is several times lower for cd1 compared to CS. This complements the traditional hypothesis that cd1 phenotype results from a mutation in phenoxazinone synthase gene governing the brown eye pigment xanthommatin synthesis. In addition to 3-HOK dimerization, cd1 mutation affects protein modification by 3-HOK. The accumulation of free 3-HOK in cd1 may result from the impairment of 3-НОК conjugation with some proteins of the brain and head tissues.